Penerapan Model Pembelajaran Problem Based Learning (PBL) terhadap Hasil Belajar Siswa SMAN 7 Palu Kelas XI pada Materi Larutan Penyangga - Beddu, Amsar T.; Sabang, Sri Mulyani; Ningsih, Purnama (Jurnal Akademika Kimia, 2018)
This research aims to investigate the result of a study in applying the model of problem-based learning (PBL) the students of SMAN 7 Palu on the topic buffer. This method use quasy experiment with pretest-posttest control group design. The population is a class XI students of SMAN 7 Palu, where the sample is a 23 students in class XI IPA 3 as the experimental group and 23 students in class XI IPA 4 as the control group, which is determined by purposive sampling. The result of student learning to the average value of the experimental class is bigger than for class control experiment was 82.61 and for the control, class is 8.65. Test normality using the Kolmogorov-Smirnov test values obtained for the experimental class Sig 0.20 > 0.05 and class control 0.20 > 0.05, it means that both at data are normally distributed. Homogeneity test using the test statistics Lavene which gained value of Fhitung 0.37 > 0.54 Ftabel for experimental classes.200 Sig > 0.05 and for grade control 0.20 > 0.05, it means that both of normally distributed data, there is similarities variant between a group or the means homogeneous. Testing hypothesis use t-test two parties where the significance value of 0.06, it means at the value of Sig > 0.05, that Ho rejected and Ha accepted. Based on the statistical test, PBL learning model on material buffer has a positive influence on results for students at SMAN 7 Palu